2018
DOI: 10.21470/1678-9741-2017-0236
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life After Open Surgical versus Endovascular Repair of Abdominal Aortic Aneurysms

Abstract: ObjectiveThis study aims to compare open surgical and endovascular aneurysm repair (EVAR) of abdominal aortic aneurysms in terms of their effects on quality of life, using Short Form-36 (SF-36).MethodsA total of 133 consecutive patients who underwent EVAR or open surgical repair for infra-renal abdominal aorta aneurysm between January 2009 and June 2014 were included in the study. Twenty-six (19.5%) patients died during follow-up and were excluded from the analysis. Overall, 107 patients, 39 (36.4%) in the ope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…A suitable method is the analysis of quality of life as subjectively experienced health from the patient’s point of view [ 23 ]. With decreased morbidity and mortality in various treatment techniques, HRQoL became a more important parameter in clinical trials [ 18 , 24 , 25 ]. The SF-36 is currently the most widely used and fast performable questionnaire for surveying HRQoL [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…A suitable method is the analysis of quality of life as subjectively experienced health from the patient’s point of view [ 23 ]. With decreased morbidity and mortality in various treatment techniques, HRQoL became a more important parameter in clinical trials [ 18 , 24 , 25 ]. The SF-36 is currently the most widely used and fast performable questionnaire for surveying HRQoL [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…They found that if the patients do not understand the postoperative impact on daily life, they are unprepared for complications and limitations during the recovery period. Several studies have reported decreased mental and physical quality of life following OR (Akbulut et al., 2018 ; Pettersson et al., 2012 ). However, from a long‐term perspective, other life circumstances also affect patients’ recovery and well‐being (Pettersson & Bergbom 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Research indicates that the adoption of Endovascular Aneurysm Repair (EVAR) offers superior outcomes compared to Open Repair (OR) [5]. Noteworthy advantages associated with EVAR include reduced perioperative mortality rates, lower complication rates, fewer needs for blood transfusions, shortened hospitalization durations, improved early-stage results, and better mental health [10]. Although decreased 30-day perioperative mortality is observed after EVAR, the OR shows significantly better results in midterm (2-6 years).…”
Section: Introductionmentioning
confidence: 99%